Learning in Forensic Chemistry Education: Impact on Criminology Students' Competence and Readiness - Charlie T. Anselmo; Jojo P. Bautista; Nissan B. Ramirez; Atty. Ariel M. Lioad; Christel A. Anselmo; Wilzar L. Gile (Future Science / FSH-PH Publications, 2025)
This study explored how e-learning influences the development of forensic chemistry skills and professional preparedness among criminology students in the Philippines. A convergent parallel mixed-methods design was utilized, incorporating a quantitative survey with 300 participants and qualitative interviews with students enrolled in a forensic chemistry course. The survey instrument, adapted from existing measures, was subjected to content validation and pilot testing, showing high internal consistency (α=0.86). Quantitative data were analyzed using descriptive statistics, correlations, and regression analyses, whereas qualitative data were analyzed using thematic analysis. The findings indicated that students had favorable views of e-learning in forensic chemistry, valued multimedia resources, and recognized both challenges and opportunities. A strong positive correlation (ρ=0.754, p=0.001) was identified between perceptions of e-learning and readiness to use e-learning tools, with readiness significantly influencing positive perceptions (R=0.708+0.806). Qualitative themes such as enrichment, utilization, enhancement, resources, and foundation underscored the advantages and disadvantages of e-learning in forensic chemistry education. The study concludes that well-crafted e-learning platforms can effectively connect theoretical knowledge with practical skills, improving students' comprehension and critical thinking. However, the absence of hands-on laboratory experience remains a significant limitation. The findings suggest that a blended learning approach, which combines e-learning with traditional practical training, is crucial for a thorough forensic chemistry education. Future research should broaden the study's scope, conduct longitudinal studies, and investigate hybrid learning models to enhance the effectiveness of e-learning in forensic chemistry education.